Joint detection-decoding of majority-logic decodable nonbinary LDPC coded modulation systems: An iterative noise reduction algorithm - Zhao, Shancheng; Wang, Xuepeng; Wang, Teng; Bai, Baoming; Ma, Xiao (2013 IEEE China Summit and International Conference on Signal and Information Processing (ChinaSIP), 2013)
In this paper, we present a low-complexity iterative joint detection-decoding algorithm for majority-logic decodable nonbinary LDPC coded modulation systems. In the proposed algorithm, a hard-in-hard-out decoder is combined with a hard-decision signal detector in an iterative manner. Each iteration consists of five phases. Firstly, the detector makes hard decisions based on the iteratively updated "received" signals; secondly, these hard-decisions are distributed via variable nodes to check nodes; thirdly, check nodes compute hard extrinsic messages; fourthly, each variable node counts hard extrinsic messages from its adjacent check nodes and feeds back to the detection node the symbol with the most votes as well as the difference between the most votes and the second most votes; finally, these feedbacks are used to shift each "received" signal point along an estimated direction to possibly reduce noise. The proposed algorithm requires only integer operations and finite field operations. Simulation results show that the proposed algorithm performs well and hence serves as an attractive candidate to decode majority-logic decodable nonbinary LDPC codes.